Volume 2: Processing 2014
DOI: 10.1115/msec2014-4054
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Drilling Incorporated Electrochemical Discharge Machining

Abstract: Electrochemical discharge machining (ECDM) is a non-conventional micromachining technology, and is highlighted for non-conductive brittle materials. However, the outcomes of ECDM have many restrictions in application due to limitations on efficiency, accuracy, and machining quality. In this paper, a drilling incorporated ECDM process is presented and analyzed to enhance material removal rate in ECDM drilling process. Incorporating micro-drilling into ECDM significantly increases the rate of material removal, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Also, high electrolyte concentration raises chemical etching of glass which rises machining depth [7]. In this study, the machining depth is raised when the applied voltage rises from 45 to 65 V. This is due to the applied voltage is primarily because of field emission law [13,18]. Figure 4 shows the mean S/N ratios plot for machined depth which indicates the effect of each parameter on machined depth.…”
Section: Effect On the Machined Depthmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, high electrolyte concentration raises chemical etching of glass which rises machining depth [7]. In this study, the machining depth is raised when the applied voltage rises from 45 to 65 V. This is due to the applied voltage is primarily because of field emission law [13,18]. Figure 4 shows the mean S/N ratios plot for machined depth which indicates the effect of each parameter on machined depth.…”
Section: Effect On the Machined Depthmentioning
confidence: 73%
“…The rotary speed of tool electrode may possibly influence the efficiency, cutting ability and quality of machining performance [13,14].…”
Section: Effect On the Machined Depthmentioning
confidence: 99%
“…Attempts have been made to address this problem in hydrodynamic regime using process modification such as vibration-assisted tool electrode. 22,23 The vibration-assisted tool electrode leads to enhancement in material removal rate (MRR) due to better circulation of electrolyte. On the contrary, an unconventional approach, that is, giving ultrasonic vibration to electrolyte has been attempted by Han et al 24 The authors revealed that ultrasonic vibrations to electrolyte in ECDM process improves machining rate owing to better flushing of electrolyte during machining of glass.…”
Section: Machining Behaviour Of Work Pieces Materials Under Ecdm Processmentioning
confidence: 99%
“…Jiang et al fabricated ECDM setup for micro-drilling on soda-lime glass material in which gravity-feed system was applied to the workpiece using the counterweight to provide the constant force. The tool spinning and vibration mechanism were provided with the help of DC motor and a piezo-actuator [17]. The gravity feed applied to a tungsten rod which was held in pin-vice and ultrasonic vibration applied to the soda lime glass material during ECDM micro-hole drilling process [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 1 N feeding force applied to the fixture using a linear guide and the pulley. The linear piezo-actuator assisted vibration on machining tool with the highest pushing force of 3000 N [20]. The constant feed force applied to the tool electrode and using PID controller the Z-axis position can control by driving a voice coil actuator which was fixed on the structure.…”
Section: Literature Reviewmentioning
confidence: 99%